Biaxial 360-degree scanning LIDAR using a liquid crystal control - Seiji Nishiwaki (Nature Portfolio, 2021)
Abstract Sophisticated non-mechanical technology for LIDARs is needed to realize safe autonomous cars. We have confirmed the operating principle of a non-mechanical LIDAR by combining concentric circular-grating couplers (CGCs) with a coaxially aligned rod lens. Laser light incident vertically on the center of the inner CGC along the center axis of the lens is radiated from the outer CGC and passes through the side surface of the lens. It is converted to a parallel beam that scans in two axes by applying voltages to two area-segmented electrode layers sandwiching the CGCs and a liquid crystal layer formed on the CGCs. We have demonstrated scanning whose motion ranges were 360 degrees horizontally and 10° vertically. A beam with a spread angle of 0.3° × 0.8° at a minimum swept vertically up to a frequency of 100 Hz and ten equally spaced beams scanned rotationally with a 6-degree cycle variation of spread of between 0.8° and 3.5°.